2017
DOI: 10.34105/j.kmel.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Application of ICT tools in communicating information and knowledge to artisanal fishermen communities in Zanzibar

Abstract: This article assesses the application of ICT tools in communicating information and knowledge to artisanal fishermen communities in Zanzibar. The study was carried out in four purposefully selected wards in Unguja District in Zanzibar, Tanzania. The study involved a sample size of 80 respondents. Data were collected by using document reviews, questionnaires, focus group discussions and personal observations. Results showed that artisanal fishermen need information and knowledge on weather condition, modern fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The transformation to open knowledge systems, called for at the global level by Cornell et al (2013) is translated into a set of recommendations in the papers we have reviewed. Elements of these open knowledge systems include collective problem framing (as shown in reviewed paper Hakkarainen et al, 2020;Newman et al, 2020), effective dialogue processes (as shown in Lestrelin et al, 2017 andRasheed andAbdulla, 2020) and open access to data and knowledge sharing (Torresan et al, 2016;Benard and Dulle, 2017) among others.…”
Section: Knowledgementioning
confidence: 99%
“…The transformation to open knowledge systems, called for at the global level by Cornell et al (2013) is translated into a set of recommendations in the papers we have reviewed. Elements of these open knowledge systems include collective problem framing (as shown in reviewed paper Hakkarainen et al, 2020;Newman et al, 2020), effective dialogue processes (as shown in Lestrelin et al, 2017 andRasheed andAbdulla, 2020) and open access to data and knowledge sharing (Torresan et al, 2016;Benard and Dulle, 2017) among others.…”
Section: Knowledgementioning
confidence: 99%